Espial: Electrochemical Soil pH Sensor for In Situ Real-Time Monitoring - Mohammed A. Eldeeb; Vikram Narayanan Dhamu; Anirban Paul; Sriram Muthukumar; Shalini Prasad (Micromachines, 2023)
We present a first-of-its-kind electrochemical sensor that demonstrates direct real-time continuous soil pH measurement without any soil pre-treatment. The sensor functionality, performance, and in-soil dynamics have been reported. The sensor coating is a composite matrix of alizarin and Nafion applied by drop casting onto the working electrode. Electrochemical impedance spectroscopy (EIS) and squarewave voltammetry (SWV) studies were conducted to demonstrate the functionality of each method in accurately detecting soil pH. The studies were conducted on three different soil textures (clay, sandy loam, and loamy clay) to cover the range of the soil texture triangle. Squarewave voltammetry showed pH-dependent responses regardless of soil texture (while electrochemical impedance spectroscopy’s pH detection range was limited and dependent on soil texture). The linear models showed a sensitivity range from −50 mV/pH up to −66 mV/pH with R2 > 0.97 for the various soil textures in the pH range 3–9. The validation of the sensor showed less than a 10% error rate between the measured pH and reference pH for multiple different soil textures including ones that were not used in the calibration of the sensor. A 7-day in situ soil study showed the capability of the sensor to measure soil pH in a temporally dynamic manner with an error rate of less than 10%. The test was conducted using acidic and alkaline soils with pH values of 5.05 and 8.36, respectively.